Efficient blind rendezvous schemes for cognitive radio ad-hoc networks - Al-Mqdashi, Abdulmajid Mohammed Ahmed (2018)
Cognitive Radio (CR) has been emerged as a promising technology for solving the spectrum scarcity and underutilization issues. The CRs allow unlicensed users, a.k.a. secondary users (SUs), to opportunistically use licensed bands without causing interference to the bands licensed users, a.k.a. primary users (PUs). Channel rendezvous is a fundamental and vital process for exchanging control messages and establishing communications between SUs in CR Ad-hoc networks (CRAHNs). Due to the major drawbacks of the dedicated common control channel (CCC) rendezvous approach, channel hopping (CH) has been emerged as an alternative approach for achieving blind rendezvous without the need of any predefined CCC. However, the absence of clock synchronization and neighborhood information as well as the spectrum heterogeneity among SUs in CRAHNs imposes great and unique design challenges for the blind CH scheme. Further challenges arise from the limitation and uctuating of channel availabilities which are varied according to the nature, dynamics, and density of PUs that are licensed to use the target spectrum. The previous research works on blind rendezvous have mainly focused on designing the CH sequence for ensuring rendezvous within a finite time while ignoring some practical issues such as the rendezvous in CRAHNs operating under fast PU dynamics or highly-dense PU networks. Besides, most of the existing works still rely on some unpractical assumptions or take long time to establish rendezvous. Therefore, designing blind rendezvous schemes that can cope with the aforementioned challenges and limitations while minimizing the rendezvous latency at the same time is an important and open area that needs to be studied and improved. In this research, efficient blind schemes are proposed to establish deterministic and fast pairwise rendezvous in different types of CRAHNs. Firstly, three CH schemes are developed for rendezvous in slow-varying CRAHNs where channel availabili- ties are not varying during the rendezvous process. The first two schemes called, Slow and Quick CH (QS-CH), and Interleaved Slow, Quick and Fixed CH (IQSF- CH), are designed to provide rendezvous in single-radio CRAHNs where each SU in the network has only a single radio. On the other hand, the third scheme called Multi-Grid-Quorum CH (MGQ-CH) is designed for multi-radio CRAHNs where SUs exploit multiple radios. The three proposed schemes utilize only the unrestricted local available channels for generating their CH sequences which is desirable in dis- tributed heterogeneous CRAHNs. Theoretical analysis and extensive simulations are conducted to demonstrate the proposed schemes efficiency in providing guaranteed rendezvous within bounded and short time-to-rendezvous (TTR). The simulation re- sults show that significant TTR reductions up to 68%, 73%, and 60% can be achieved by the proposed single-radio and multi-radio schemes, respectively, as compared to other related previous works in the literature. Second, two adaptive nested cyclic-quorum-based CH schemes, called NCQ-CH and MNCQ-CH, are proposed for rendezvous in fast-varying CRAHNs where channel availabilities can vary during the rendezvous process. The proposed schemes are augmented with efficient channel ranking and quorum selection mechanisms for gen- erating and adapting the CH sequence on the y which make them robust to the fast PU dynamics. The simulations results show that the proposed schemes can reduce the TTR up to 49%, as compared to other existing adaptive CH schemes while providing better PU detection accuracy. Finally, two blind coprimality-based sector hopping (SH) schemes called, Prime and Even SH (PES-SH), and Interleaved PES-SH (IPES-SH), are proposed to establish sector rendezvous in directional antenna CRAHNs where SUs are equipped with single directional antenna CRs. The proposed SH schemes are then combined with a Ranked Quick and Slow CH (RQS-CH) scheme in order to establish simultaneous sector and channel rendezvous. The theoretical analysis and simulations results demonstrate the developed schemes efficiency where they can reduce the rendezvous delay significantly up to 85% and 55%, as compared to other existing related works. Furthermore, the results demonstrate that the proposed schemes are more resistant to rendezvous failures under high density PU networks, as compared to the omni- directional antenna rendezvous paradigm.